Extraction of protein from churpi of yak milk origin: Size reduction, nutraceutical potential and as a wall material for resveratrol. (April 2022) - Gani, Asir; Noor, Nairah; Gani, Adil; Joseph-Leenose-Helen, Jenno; Shah, Asima; Ashraf, Zanoor ul
Abstract: Resveratrol is a known anti-oxidant and anti-cancer bioactive. The low bioavailability and poor water solubility of resveratrol is a major barrier that restricts its usage in food applications. To overcome these problems, the study presents micro and nano encapsulation of resveratrol in casein micelles extracted from Himalayan cheese ( Churpi ). Resveratrol loaded casein microparticles (CS-rm) were obtained using emulsion-freeze drying. Whereas, resveratrol loaded casein nanoparticles (CS-rn) were obtained using ultrasonication. Both were characterized using dynamic light scattering (DLS), scanning electron microscopy (SEM) and attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR). DLS revealed hydrodynamic diameter of 71.24 μm and 387.023 nm and zeta potential of −22.62 and −28.08 mV for CS-rm and CS-rn. FTIR confirmed the characteristic peaks of resveratrol at 965.4, 1380.86, 1586.66 and 1607 cm −1 confirmed successful micro and nanoencapsulation. CS-rm displayed high encapsulation efficiency (52.32%) and swelling power (77.90 at pH 3 and 68.65 at pH 7.5) than CS-rn. Both micro and nanoencapsulation protected resveratrol in gastric conditions, however, CS-rn showed high release of resveratrol then CS-rm in simulated intestinal conditions. The anti-oxidant and anti-cancer activity of resveratrol under simulated gastric and intestinal conditions (SGID) was significantly higher (p ≤ 0.05) for CS-rn, showing that nanoencapsulation improved release and nutraceutical profile of resveratrol. Resveratrol loaded nano and micro casein particles can be used a source of fortified protein supplement in growing food and nutraceutical industry.